1986
DOI: 10.1042/bj2400277
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fatty acids and starvation on the metabolism of gluconeogenic precursors by isolated sheep liver cells

Abstract: Isolated liver cells prepared from fed sheep synthesize glucose from propionate at twice the rate observed with cells from starved animals. Addition of palmitate or palmitate + carnitine to incubations of liver cells from starved animals inhibited the rate of glucose synthesis with lactate as a precursor, but had little effect when propionate and pyruvate were substrates. Liver cells from fed and starved sheep synthesized lactate and pyruvate when incubated with propionate. Fatty acids inhibited this formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…It has been suggested that fasting periods are not a confounding factor when determining glucose curve concentrations in adult ruminants (Kaneko, 2008) due to limited intestinal glucose absorption (Reynolds et al, 1988). In vitro studies conducted in sheep have shown that liver cells derived from fed animals had higher glucose synthesis rates than cells cultured from fasted animals (Lomax et al, 1986). The results from our study demonstrate that basal glucose concentrations are affected by the length of fasting period, predominantly at 24, 36, and 48 h. On the other hand, similar glucose concentrations were found when 12-h food-deprived females were compared with animals without feed restriction, which might be attributed to the effects of rumen content on nutrient availability.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that fasting periods are not a confounding factor when determining glucose curve concentrations in adult ruminants (Kaneko, 2008) due to limited intestinal glucose absorption (Reynolds et al, 1988). In vitro studies conducted in sheep have shown that liver cells derived from fed animals had higher glucose synthesis rates than cells cultured from fasted animals (Lomax et al, 1986). The results from our study demonstrate that basal glucose concentrations are affected by the length of fasting period, predominantly at 24, 36, and 48 h. On the other hand, similar glucose concentrations were found when 12-h food-deprived females were compared with animals without feed restriction, which might be attributed to the effects of rumen content on nutrient availability.…”
Section: Discussionmentioning
confidence: 99%
“…Their contribution varies with the balance between availability in gluconeogenic precursors, whole body glucose demand and utilization as well as whole body AA demand (Kraft, 2009). During body store mobilization as in feed restriction or lactation, contribution of endogenous precursors (in particular AAs from muscle proteolysis) increases (Lomax et al, 1986). It is also the case when glucose demand increases, such as after phlorizin treatment of lactating cows (Overton et al, 1999).…”
Section: Metabolism Of Vfa and Glucose By Portal-drained Visceramentioning
confidence: 98%
“…Following a 16-h fast, they found circulating glucose concentrations of neonatal rats injected with glucogenic substrates to increase 2-fold (from 1.1 to 2.6 mM), whereas a similar injection into rats previously fed triglycerides increased blood glucose 4-fold (from 1.1 to 4.7 mM; Ferre et al, 1978). Based on in vitro work with sheep hepatocytes, Lomax et al (1986) proposed that reducing equivalents from fatty acid metabolism affect the transport of carbon atoms across the mitochondrial membrane. This is of particular importance when shuttling malate carbon during gluconeogenesis in the transition dairy cow.…”
Section: Introductionmentioning
confidence: 99%